Perjuangan Kisah Cinta Tokoh Utama dalam Novel The Sun Is Also A Star Karya Nicola Yoon - Klarisa; Saprudin (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2022)
This research is entitled The Love Story of the main character in the novel The Sun Is also A Star by Nicola Yoon. The main character named Natsha Kingsley, a Jamaican girl who is tall in New York City is struggling against the deportation that the American government will carry out against her family. Natasha is also a realistic woman who doesn't believe in love and is struggling to keep her family from being deported. However, her meeting with Daniel by chance, makes things complicated. Therefore, the American government plans to deport them today. This study aims to describe how the main character in Nicola Yoon's novel The Sun Is Also A star and the struggle of the main character's love story in Nicola Yoon's novel The Sun Is Also A Star. The research method used is descriptive qualitative method. Descriptive qualitative research is one of the types of research that is included in the type of qualitative research. The purpose of this research is to reveal events or facts, circumstances, phenomena, variables and circumstances that occurred during the research by presenting what actually happened. The approach applied is the Sociology of Literature. Sociology of literature is a reflective branch of literary research. This research is in great demand by researchers who want to see literature as a mirror of people's lives. Sociology of literature is research that focuses on human problems.